2017
DOI: 10.1021/acs.biochem.7b00291
|View full text |Cite
|
Sign up to set email alerts
|

Solution Conformations and Dynamics of Substrate-Bound Cytochrome P450 MycG

Abstract: MycG is a P450 monoxygenase that catalyzes the sequential hydroxylation and epoxidation of mycinamicin IV (M-IV), the last two steps in the biosynthesis of mycinamicin II, a macrolide antibiotic isolated from M. griseorubida. The crystal structure of MycG with M-IV bound was previously determined, but showed the bound substrate in an orientation that did not rationalize the observed regiochemistry of M-IV hydroxylation. NMR paramagnetic relaxation enhancements (PRE) gave evidence for an orientation of M-IV in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…The methodology used to generate the solution structures discussed here has been detailed in previous publications 9 , 11 , 12 . In brief, sequential resonance assignments for backbone amide 1 H, 15 N correlations in MycG were made using multidimensional NMR data sets obtained with a combination of uniformly and type-selective 2 H, 13 C and 15 N labeled samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The methodology used to generate the solution structures discussed here has been detailed in previous publications 9 , 11 , 12 . In brief, sequential resonance assignments for backbone amide 1 H, 15 N correlations in MycG were made using multidimensional NMR data sets obtained with a combination of uniformly and type-selective 2 H, 13 C and 15 N labeled samples.…”
Section: Resultsmentioning
confidence: 99%
“…Solution NMR permits tight control of conditions (e.g., oxidation state, ligands/substrates, ionic strength) so that the relevance of structure and dynamics to a given point in the reaction pathway can be more readily assessed 1 . Chemical shift perturbation and dynamics measurements provide insight into those structural features that are involved in substrate and effector recognition 4 8 , and residual dipolar couplings (RDCs) can be used to characterize enzyme conformations that are populated as a function of substrate or effector binding 9 – 13 . We have previously used RDC-directed “soft annealing” molecular dynamics simulations to show that CYP101A1 (cytochrome P450 cam ) undergoes significant conformational changes upon binding of substrate d -camphor 11 , 12 , and via site-directed mutagenesis coupled with activity assays, demonstrated that the observed changes are not artifacts of the methodology, but reliable representations of the conformational equilibria accessed by CYP101A1 in the presence and absence of substrate 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our data on OleP and on structures of other bacterial P450s such as P450 cam , P450 monooxygenase from Streptomyces venezuelae (PikC), P450 C12-hydroxylase from Streptomyces erythraeus (EyrK), P450 monooxygenase from Bacillus megaterium (P450BM3), P450 monooxygenase from Sulfolobus solfataricus (CYP119A), and mycinamicin monooxygenase from Micromonospora griseorubida (MycG) (8,10,11,(43)(44)(45)(46)(47), we support the mechanism of substrate sensing by the conserved A/G n21 -G n -XX-T n+3 motif in the center of the I helix (12) which allosterically drives transitions within the protein fold as a general feature of biosynthetic bacterial P450s and as the basis of the regulation of potentially detrimental oxygen activation. Consequently, substrate-bound bacterial P450 structures where catalytic competence signatures are missing (i.e., water channel and cleft on the I helix, heme pentacoordination), should be considered as preactivation complexes requiring further rearrangements to reach the competent conformation for catalysis (9).…”
Section: Discussionmentioning
confidence: 99%
“…Structural studies of two such enzymes have indicated that only small changes in the positioning of the substrate relative to the heme prosthetic group are required to achieve the successive oxidation reactions, because the atoms undergoing functionalization are positioned adjacent to each other. [8][9][10] Several plant-pathogenic Actinobacteria, including Streptomyces acidiscabies, Streptomyces turgidscabies and Streptomyces scabies, produce thaxtomins, a family of phytotoxic diketopiperazines that inhibit cellulose biosynthesis in expanding plant tissues. 11 S. scabies causes common scab in potatoes and other economically important crops, 12 and thaxtomin A 1 has been approved by the EPA for use as an herbicide (registration number: 84059-12), although it has yet to reach the market.…”
Section: Introductionmentioning
confidence: 99%